A Different Shade of Justice : Asian American Civil Rights in the South - Hinnershitz, Stephanie, 1984- (Book collections on Project MUSE., 2017)
In the Jim Crow South, Chinese, Filipino, Japanese, and, later, Vietnamese and Indian Americans faced obstacles similar to those experienced by African Americans in their fight for civil and human rights. Although they were not black, Asian Americans generally were not considered white and thus were subject to school segregation, antimiscegenation laws, and discriminatory business practices. As Asian Americans attempted to establish themselves in the South, they found that institutionalized racism thwarted their efforts time and again. However, this book tells the story of their resistance and documents how Asian American political actors and civil rights activists challenged existing definitions of rights and justice in the South. From the formation of Chinese and Japanese communities in the early twentieth century through Indian hotel owners'battles against business discrimination in the 1980s and'90s, Stephanie Hinnershitz shows how Asian Americans organized carefully constructed legal battles that often traveled to the state and federal supreme courts. Drawing from legislative and legal records as well as oral histories, memoirs, and newspapers, Hinnershitz describes a movement that ran alongside and at times intersected with the African American fight for justice, and she restores Asian Americans to the fraught legacy of civil rights in the South.